1293 Timely TPN – A comparative study reviewing the administration of TPN for preterm infants following implementation of NICE guidelines. (17th August 2022) - Madabhushi, Spandana Rupa; Ahmed, Syed Ather
Abstract : Aims: Preterm infants are born with an immature gastrointestinal tract and less nutritional reserve, with the risk of postnatal growth failure and long term neurocognitive sequela if these needs are not addressed. Early administration of parenteral nutrition is recommended with regional guidelines using absolute criterion based around gestation or birthweight to determine the need for this form of nutrition. In 2020, NICE updated their guidance for administration of parental nutrition in preterm neonates, advocating a gestational cut-off of less than 31 weeks and introducing an 8 hour administration window. Our level 2 unit admits any baby with a gestation greater than 27 weeks, and this comparative study evaluates the management of these neonates before and after implementation of this guidance. Methods: Quantitative data was collected between 01/12/2019 till 30/9/2021, both pre and post local implementation of the new guidance. Enteral feeds were introduced and built up based upon standardised East of England regional feeding guidelines, and this was the same for both groups. Forty-five neonates who were started on parenteral nutrition were identified and their records reviewed. Of these, twenty-three were excluded as they were ex-utero transfers or above the gestational age threshold. Results: Table 1 compares the management of infants born pre and post-implementation of the new guidance. The results show that post implementation, parenteral nutrition and enteral feeds are started sooner. However there is no effect on time to reach full enteral feeds. Reassuringly, the 8 hour administration window has not led to any catheter associated infections. Conclusion: In summary, these results illustrate the early successes of the implemented pathway with a large proportion of infants receiving parenteral nutrition in a timely fashion. Although our study has limited numbers, there was no difference noted in time to reach full enteral feeds from when the parenteral nutrition was started. Further evaluation is required to determine the impact this guidance has on time to reach full enteral feeds. We acknowledge the practical difficulties faced when it came to obtaining timely central access especially when these infants were born out-of-hours. It would be interesting to compare the compliance and data from similar level two units and tertiary centres around the UK who have adopted the updated NICE guidance. References: National Institute for Health and Care Excellence (2020) Neonatal Parenteral Nutrition, Available at www.nice.org.uk/guidance/ng154 Radbone L (2019), Parenteral Feeding of Infants on the Neonatal Unit, East of England Perinatal Networks.